2017
DOI: 10.1177/0954406217722378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the screw–nut joint stiffness on the position-dependent dynamics of a vertical ball screw feed system without counterweight

Abstract: The study on the position-dependent dynamic characteristics of a vertical ball screw feed system without counterweight is an important step in the enhancement of the structural performance of mini-type vertical milling machines. The ball screw is generally driven by a servomotor, which converts a rotary motion into a linear motion through a screw–nut pair. To assess the position-dependent dynamic characteristics of a vertical ball screw feed system subjected to the influence of the screw–nut joint stiffness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…The transmission stiffness in the transmission direction consists of the axial stiffness of both the upper and lower sections of the screw shaft and the equivalent axial stiffness of the screw-nut joints and bearing joints, as shown in Figure 2. Therefore, the transmission stiffness under upward acceleration in the transmission direction can be calculated as Similarly, the transmission stiffness under upward deceleration in the transmission direction can be calculated as (28)…”
Section: Calculation Of Transmission Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission stiffness in the transmission direction consists of the axial stiffness of both the upper and lower sections of the screw shaft and the equivalent axial stiffness of the screw-nut joints and bearing joints, as shown in Figure 2. Therefore, the transmission stiffness under upward acceleration in the transmission direction can be calculated as Similarly, the transmission stiffness under upward deceleration in the transmission direction can be calculated as (28)…”
Section: Calculation Of Transmission Stiffnessmentioning
confidence: 99%
“…Optimal design modifications, structural dynamics simulations, and stability assessments were simultaneously carried out. On this basis, Zou et al [28] discussed the influence of the screw-nut joint stiffness on the position-dependent dynamics of a vertical ball screw feed system without counterweight and found that the spindle system counterweight should be considered when estimating the dynamics of a vertical ball screw feed system without counterweight. Therefore, in this study, the dynamics of a vertical ball screw feed system without counterweight under acceleration and deceleration are investigated considering the spindle system weight.…”
Section: Introductionmentioning
confidence: 99%
“…The ball screw is a transmission device that converts linear motion into rotary motion or rotary motion into linear motion, and it has the advantages of high position accuracy, load capacity and fatigue life [1][2][3]. The dynamic characteristic of the feed system is the key factor to determine the machining accuracy of the workpiece and stability of the cutting process [4,5], and the nonlinear contact relationship between balls and raceways leads to the complexity and instability of the worktable vibration [6,7]. Therefore, the establishment of a dynamic model of the feed system is of great significance to improve the machining accuracy and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al studied the influence of screw-nut stiffness on the vibration characteristics of the spindle system in the transmission direction. Based on the equivalent dynamic equation and the D'Alembert's principle, the varying-coefficients model of feed system was established, but the influence of coupling characteristics was neglected [7]. Vicente et al established a mathematical model, which is coupled with torsional and axial system by using Ritz series method, to analyze the influence of lead and workbench position [8].…”
Section: Introductionmentioning
confidence: 99%